Axial strain effect on translational motion property of carbon nanotube thermal actuator. Issue 17 (21st November 2020) - Huang, Jianzhang; Fan, Yue; Guo, Yalan; Liang, Yingjing
ABSTRACT: The possibility of strain engineering of linear motion property of the double walled carbon nanotube thermal actuator is explored in this paper. Systematical study of axial strain effect on linear motion property of the carbon nanotube thermal actuator is conducted using molecular dynamics, and real-time controlling method for double walled carbon nanotube thermal actuator by applying axial strains is proposed as well. It is found that the axial strain has great influences on the linear motion behaviour of the thermal actuator, implying that the strain effect has potential to control the property of nano actuator. The strain effect and its mechanism are revealed by investigating the variation of thermal driving force and intertube distance as the axial strain is applied. The intertube interaction affected by axial strain is analyzed using the intertube stiffness constant drawn from the analytical model. The valuable conclusions for strain engineering of nanoscale actuator are obtained. This work suggests the great potential of strain effect to be real-time control method to nanoelectromechanical system and provides new ideas for the application of carbon nanotube thermal actuator.